2021
DOI: 10.1111/wbm.12239
|View full text |Cite
|
Sign up to set email alerts
|

Japanese knotweed control with winter soil injection of chemicals targeting the rhizome system

Abstract: To achieve chemical control of aggressive creeping perennial weeds and avoid the disadvantages of conventional foliar applications, we established a winter soil‐injection method using soil‐active herbicides. Our previous study demonstrated the feasibility of the practical use of this method by showing that the regeneration from rhizomes or creeping root segments was inhibited by direct contact with chemicals in the soil. Then, a field trial was conducted on a population of Japanese knotweed. A stand of 148 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, an alternative explanation might lie in the potential for better, more complete coverage of the systemic herbicide applied in mid‐summer, simply as a function of reduced canopy area (Boyd et al, 2017). Our data do not allow us to distinguish these two alternatives, but does suggest that optimizing long‐term control of knotweed using sequential contact and systemic herbicide treatments warrants additional testing; ideally, these would include examination of the interactive effects on above and belowground systems (Ito & Ito, 2021; Kadlecová et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, an alternative explanation might lie in the potential for better, more complete coverage of the systemic herbicide applied in mid‐summer, simply as a function of reduced canopy area (Boyd et al, 2017). Our data do not allow us to distinguish these two alternatives, but does suggest that optimizing long‐term control of knotweed using sequential contact and systemic herbicide treatments warrants additional testing; ideally, these would include examination of the interactive effects on above and belowground systems (Ito & Ito, 2021; Kadlecová et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
“…However, eradication of knotweed ultimately demands reduction of rhizome activity and viability (Bashtanova et al, 2009), which have been shown to vary with treatment timing (Kadlecová et al, 2022). We recommend that future studies of sequential applications should include assessment of changes in belowground and aboveground growth (Ito & Ito, 2021; Kadlecová et al, 2022); ideally these would be implemented as long‐term field‐based designs that can help inform management (Jones et al, 2018; Kadlecová et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Managing invasive knotweeds is challenging due to their ability to accumulate significant below-ground reserves, allowing them to recover from various control methods, including physical, biological, chemical, and integrated approaches [ 19 , 20 , 21 , 22 ]. In the case of Japanese knotweed, some success has been achieved by focusing on seasonal resource translocation between above- and below-ground biomass and using suitable herbicide coverage or injections, such as glyphosate [ 19 , 20 , 21 , 22 ]. Another method involves physically burying rhizomes and stems [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…All invasive knotweeds are di cult to control, as minimum disturbance regimes permit the accumulation of signi cant below-ground reserves that allow recovery from many physical, biological, chemical, and integrated control methods. According to a few authors, in the case of Japanese knotweed, an approach that works with the seasonal resource translocation between above-and below-ground biomass and adequate herbicide coverage or injections, e.g., glyphosate, is the key to success 19,20,21,22 . The other adopted methods are the physical burying of rhizomes and stems 23 .…”
Section: Introductionmentioning
confidence: 99%